OPTIMIZATION OF RHAMNOLIPID BIOSURFACTNT PRODUCTION BY STREPTOMYCES MATENSIS (NBRC 12889T) USING PLACKETT-BURMAN DESIGN - Prabhakar T2Kalyani A.L.T1*, Girija Sankar G2 (Journal of Biomedical and Pharmaceutical Research, 2014)
Surfactants produced by microorganisms are known as biosurfactants. Biosurfactants are becoming important biotechnology products for industrial and medical applications due to their specific modes of action, low toxicity, relative ease of preparation and widespread applicability. In the present study, Streptomyces matensis (NBRC 12889T), the biosurfactant producing Actinomycetes, was isolated from soil contaminated with poultry litter near Visakhapatnam, India. The isolated strain was grown in Kim’s medium for extracellular biosurfactant production and it was identified as Rhamnolipid biosurfactant by Orcinol assay taking L-Rhamnose as standard. Further Optimization of medium constituents present in Kim’s medium was done by the Plackett-Burman design. Among the seven medium constituents, three variables, namely concentration of Olive oil, NaNO3 and level of inoculums were identified to cause significant effect on the biosurfactant production. By using the optimal fermentation medium, biosurfactant production was improved to 344.99 µg/ml compared to the unoptimized medium which was 315.93 µg/ml, an increase of 9.2 %. By this the Plackett-Burman design can be powerfully used to improve biosurfactant production by Streptomyces matensis (NBRC 12889T) as a function of various salt compositions and levels of ingredients in the production medium. Key words: Streptomyces matensis, Actinomycetes, Rhamnolipid, Fermentation, Kim’s medium.